Clinical effectiveness and cost-effectiveness of cholecystectomy compared with observation/conservative management for preventing recurrent symptoms and complications in adults presenting with uncomplicated symptomatic gallstones or cholecystitis : a systematic review and economic evaluation /: a systematic review and economic evaluation. (August 2014) - Brazzelli, M (Miriam)
No abstract available